Prevalence of self-medication with antibiotics among adolescents with suspected genital infection in the Ngiri-Ngiri health zone in Kinshasa, Democratic Republic of the Congo (International Journal of Agricultural Research, Innovation and Technology, 2025)
Adolescents are among the groups most exposed to Sexually Transmitted Infections (STIs) and most likely to resort to self-medication, which constitutes a threat to public health. This study aimed to assess self-medication practices for symptoms of sexually transmitted infections (STIs) among adolescents in the commune of Ngiri-Ngiri in the City of Kinshasa, Democratic Republic of the Congo. This cross-sectional descriptive study was conducted by interviewing 224 adolescents using ODK software. Data were processed with XLSTAT. Of the 224 adolescents, 34.3% admitted to having symptoms associated with STIs. The prevalence of self-medication with antibiotics was 45.5%. Of those who self-medicated, 70% attended school, 47% were male, and 53% were female. Of all the drugs used, amoxicillin ranked first, followed by penicillin, vaginal ovules, and tetracycline. The study also showed that some women resorted to phytotherapy. As for the source of information, 70% of teenagers confirmed that they had obtained this information from pharmacy owners, 29% from the community, and 23% from healthcare providers. Given the considerable prevalence of self-medication for symptoms associated with STIs in this environment, health workers and political decision-makers are called upon to pool their efforts to raise awareness of the rational use of medicines to reduce or even eradicate this harmful practice.Int. J. Agril. Res. Innov. Tech. 15(1): 147-154, June 2025